From pilots to county-wide change: Scaling gender-transformative innovation bundles in Embu, Kenya - Nchanji, Eileen Bogweh; Lutomia, Cosmas; Nyamolo, Victor (2025)
Farmers in Embu, Kenya, are scaling Gender Transformative Innovation Bundles (GTSTIBs) from pilots to county-wide adoption, empowering women, youth, and PWDs for resilient, equitable and sustainable agriculture. In the rolling hills of Embu, a quiet revolution is taking root. For years, smallholder farmers—especially women and young people—have faced challenges including poor yields, changing climates, and limited market access. But something new is happening: farmers are not just receiving innovations, they are co-creating them. Welcome to the world of Gender Transformative Socio-Technical Innovation Bundles (GTSTIBs)—a mouthful, yes, but in simple terms, it means bringing together seeds, tools, knowledge, and conversations that empower farmers as equals.